Case report of a 45-year old female Fabry disease patient carrying two alpha-galactosidase A gene mutation alleles. Issue 1 (December 2016) - Oder, Daniel; Vergho, Dorothee; Ertl, Georg; Wanner, Christoph; Nordbeck, Peter
Abstract Background X-chromosomal inheritance patterns and generally rare occurrence of Fabry disease (FD) account for mono-mutational hemizygous male and heterozygous female patients. Female mutation carriers are usually clinically much less severely affected, which has been explained by a suggested mosaicism in cell phenotype due to random allele shutdown. However, clinical evidence is scarce and potential additional effects in female gene carriers, which might account for specific clinical characteristics such as less severe chronic kidney disease, are yet unknown. Case presentation This article reports on a 45 year old female patient carrying the two alpha-galactosidase A gene mutations c.416A > G, p.N139S in exon 3 and c.708G > C, p.W236C in exon 5, but still showing only mild organ manifestations. Conclusion This current case highlights the importance of careful clinical characterization in patients with Fabry disease, who may show additional rare constellations and, therefore, are in need of personalized medicine. The impact of potential additional protective effects exceeding the presence of a non-pathogenicGLA allele in female gene carriers requires further investigation.